2016
DOI: 10.5194/acp-16-13173-2016
|View full text |Cite
|
Sign up to set email alerts
|

The open-ocean sensible heat flux and its significance for Arctic boundary layer mixing during early fall

Abstract: Abstract. The increasing ice-free area during late summer has transformed the Arctic to a climate system with more dynamic boundary layer (BL) clouds and seasonal sea ice growth. The open-ocean sensible heat flux, a crucial mechanism of excessive ocean heat loss to the atmosphere during the fall freeze season, is speculated to play an important role in the recently observed cloud cover increase and BL instability. However, lack of observations and understanding of the resilience of the proposed mechanisms, esp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Thus, the global average surface albedo is 24 185 = 0.13 = 13 %. The values for cloud albedo and atmospheric (Ganeshan and Wu, 2016). Finally, for the purposes of sensible and latent heat transport (see appendix), the wind speed U is 5 m s −1 (Nugent et al, 2014) and the drag coefficient is C D = 1.5 × 10 −3 .…”
Section: Ebm For Globally Averaged Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the global average surface albedo is 24 185 = 0.13 = 13 %. The values for cloud albedo and atmospheric (Ganeshan and Wu, 2016). Finally, for the purposes of sensible and latent heat transport (see appendix), the wind speed U is 5 m s −1 (Nugent et al, 2014) and the drag coefficient is C D = 1.5 × 10 −3 .…”
Section: Ebm For Globally Averaged Temperaturementioning
confidence: 99%
“…Today, there is widespread agreement that the climate of the Earth is changing, but the precise trajectory of future climate change is still a matter of debate. Recently there has been much interest in the possibility of "tipping points" (or bifurcation points) at which abrupt changes in the Earth climate system occur (see Brovkin et al, 1998;Ghil, 2001;Alley et al, 2003;Seager and Battisti, 2007;Lenton et al, 2008;Ditlevsen and Johnsen, 2010;Lenton, 2012;Ashwin et al, 2012;Barnosky et al, 2012;Drijfhout et al, 2015;Bathiany et al, 2016;North and Kim, 2017;Steffen et al, 2018;Dijkstra, 2019;Wallace-Wells, 2019). Section 12.5.5 in IPCC (2013) gives an overview of such potential abrupt changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in transitional seasons (i.e., spring and autumn), the influencing factors on the PBLH are more complex. These include rapidly changing atmospheric circulation patterns and atmospheric conditions (Ganeshan & Wu, 2016). In addition, our subsequent research in Section 3.1.1 also found that high sea ice concentration ( SIC ) also has a significant impact on the differences in PBLH from ERA5 and observations especially in spring and autumn.…”
Section: Resultsmentioning
confidence: 99%
“…The slightly lower, but spatially consistent, low-tropospheric temperatures in the CLD3 experiment result from the differences in the type of AIRS radiances assimilated and their associated coverage, as noted in Figure 1. The Arctic atmosphere has abundant low-level clouds associated with mid-tropospheric subsidence that are sensitive to the stability of the lower troposphere (Barton et al, 2012;Taylor et al, 2015;Ganeshan and Wu, 2016). It is possible that assimilation of CCRs in the CLD3 experiment is effective in capturing an important Arctic feature that would be missed by clear-sky data.…”
Section: Impact On the Analyzed Representation Of The Arctic Tropospherementioning
confidence: 99%